When will the 2015 millennium development goal of infant mortality rate be finally realised? – Projections for 21 OECD countries through 2050. (2018) - Chang, Yu Sang; Lee, Jinsoo; Kwon, Hyuk Ju
According to the United Nations Children's Fund (UNICEF), the number of global infant deaths for those under the age of one year was down from 8.4 million in 1990 to 5.4 million in 2010. However, the declining trend of infant mortality rate varies significantly from country to country based on the vastly different environmental elements they face. This paper attempts to predict the future infant mortality rate of 21 OECD countries through 2015 and 2050 by the use of experience curve model and compare the results to the two other well-known projections by the United Nations Population Division and the US Census Bureau in the context of the millennium development goal targets. The results from all three projections indicate that only one or two countries will meet the two-thirds reduction target of the 2015 millennium development goal. By 2050, four to 18 countries will still not be able to meet the target. Therefore, each country may need to undertake a comprehensive review of its policies and programs of infant mortality control to generate many alternative plans for major improvement.